(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The aim of the study was to devise soft skills development strategies for Computer Engineering and Information Technologies undergraduate students in the process of learning English. The research consisted of total 347 Computer Engineering and Information Technologies undergraduate students including 45 female students (13.00%) and 302 male students (87.00%) aged from 17 to 21. The research which was non-experimental in nature was conducted at four higher education institutions in Ukraine between October 2020 and November 2020. To reach the main aim of the study the team of researchers developed a web-based questionnaire containing open-ended and closed-ended questions. The use of the web-based questionnaire seemed to be quite logical for collecting the data necessary for devising soft skills development strategies for Computer Engineering and Information Technologies undergraduate students in the process of learning English taking into account the situation connected with the Covid-19 pandemic. The respondents who volunteered to take part in the survey were sent a link to the web-based questionnaire and guaranteed the complete anonymity. The data analysis covered processing of information collected from the anonymous web-based survey, displaying the data obtained in the form of tables and figures, devising soft skills development strategies based on research results and drawing general conclusions. The findings obtained enabled the authors to present six development strategies aimed at enhancing soft skills among Computer Engineering and Information Technology undergraduate students that could be applied in the process of learning English: a) combination of competence-based, action-oriented and blended-learning approaches in the English for Specific Purposes classroom, b) integration of formal, non-formal and informal learning, c) participation in specially focused network professional communities, d) use of open educational resources for learning English, e) use of open professionally-oriented educational resources, f) introduction of learning-style based activities in the English for Specific Purposes classroom for boosting students’ soft skills.